Estimates for the elastic moduli of 2D aggregate of hexagonal-shape orthorhombic crystals with in-plane random crystalline orientations - Hanh, Vuong Thi My; Chau, Le Hoai; Dong, Vu Lam; Chinh, Pham Duc (Vietnam Journal of Mechanics, 2019)
Numerical finite element simulations on the homogenization problem for large samples of particular 2D hexagonal-shape-geometry random orientation aggregates from the base crystals of orthorhombic symmetry have been performed. At sufficiently large random-aggregate samples, the scatter intervals of the macroscopic 2D bulk and shear elastic moduli converge toward the Voigt-Reuss-Hill bounds, and then our recently constructed theoretical estimates, which have been specified for the aggregates.